Orpheus Britannicus - Purcell, Henry 1659-1695 (London Playford, 1706)
'Orpheus Britannicus' is a collection of songs by Henry Purcell, published posthumously in London in two volumes, the first in 1698 and the second in 1702.
Inserted engraved portrait of Purcell by R. White based on the portrait painted by John Closterman (1660-1711). This engraving seems to be from a later edition, pasted on the frontispiece page.
The second edtion of the first book contains 34 songs that are not included in the first edition
Book one at p. 148 has a manuscript note "To be sung by a Countertenor" next to the Song 'The Fife'
front matter contains inserted manuscript index of book 1
Vol. 1 was originally published in 1698
Ex librs S. H. Sutherland (manuscript)
Keywords: 17th Century (1601-1700); Song; Instrumental music; London (United Kingdom)